Finite Element Analysis on Inelastic Mechanical Behavior of Composite Beams Strengthened With Carbon-Fiber-Reinforced Polymer Laminates Under Negative Moment - Song, Aiming; Xu, Hongtao; Luo, Qi; Wan, Shui (Frontiers in Materials, 2022)
This paper studies the improvement in the inelastic mechanical property of steel-concrete composite beams strengthened by carbon-fiber-reinforced polymers (CFRP) laminates under negative moment. Firstly, the monotonic loading test was designed and performed on an inverted simply supported beam to simulate the negative moment regions of continuous composite beams. Secondly, the finite element analysis (FEA) on flexural capacity and cracking resistance in negative moment regions of composite beams was carried out with ANSYS software. A series of mechanical indexes including load-deflection curve, component strain and crack propagation were obtained from the FEA model and verified through the test data. The results showed that the FEA model can accurately predict the general mechanical behavior of composite beams under negative moment, and the calculation results considering the interface slip effect were closer to the experimental values. Finally, based on the FEA model, the parametric study on static behavior in negative moment regions of composite beams strengthened with / without CFRP laminates were conducted. The effects of CFRP layout width, layout position, layer number, longitudinal reinforcement ratio and shear connection degree on the bearing capacity of composite beams were considered. The CFRP laminates can effectively improve the bending resistance of composite beams under negative moment. At a low reinforcement ratio, the bearing capacity was greatly affected by the layout width and layer number of CFRP laminates, but the rate of increase was not significant when the layer number was more than 3. The reinforcement ratio had a great influence on the bearing capacity of composite beams under negative moment, but the influence of shear connection degree was not remarkable.